Ecoversity: the potential for sustainable development to reshape university culture and action. (4th October 2010) - Hopkinson, Peter
This paper describes an institutional strategy (Ecoversity) to embed sustainable development across the full range of university activities and services and reflects on two different phases of Ecoversity providing illustrations and case examples of specific actions and changes that have occurred. The programme has begun to deliver tangible benefits to the institution and has begun to act as a catalyst for, and link up with other, internal initiatives that are seeking to reshape the university culture and core activities around sustainable development. The paper reflects on the process of change and describes a process model that captures many of the key elements that needed to be addressed to initiate change and scale up activities. The process model is helpful in analysing barriers to change and how change can be achieved. The project illustrates a conscious and deliberate process for embedding SD within a university culture and offers a coherent conceptual framework for describing change processes.